무형유산 경기검무의 문화콘텐츠 적용과 활용 고찰 - 이주영; Lee Joo Young; 배소연; Bae So Youn (국제문화예술, 2022)
연구목적: 이 논문의 목적은 무형문화재인 경기검무의 무형유산의 가치에 기반 해 문화콘텐츠 적용과 활용 방안을 모색하는데 주안점을 두고 있다. 연구방법: 문헌 연구 및 기존 선행연구를 통해 무형문화재인 경기검무의 당대적 가치가 반영된 문화콘텐츠 적용과 활용 방안을 모색한다. 이를 위해 무형유산의 의의와 경기검무의 특징을 진단한다. 경기검무의 문화콘텐츠 적용과 활용을 위해 세 가지 축을 상정한 후, 다음의 결과를 도출했다. 연구결과: 첫째, 지역 고유성 기반 경기검무 문화콘텐츠 방안으로는 정례화된 경기검무 페스티벌 개최다. 둘째, 민족 대표성 기반 경기검무 문화콘텐츠 방안은 검무 콘텐츠 플랫폼 조성과 운영이다. 셋째, 예술 전승성 기반 경기검무 문화콘텐츠 방안으로는 21세기 무형유산 경기검무 문화콘텐츠로의 다각적 적용이다. 결론: 무형유산 경기검무는 문화원형의 고유성, 전통춤이 지닌 내재성이 다양한 플랫폼과의 접목을 통해 적용과 활용이 가능함을 확인했다. Purpose: The purpose of this paper is to find ways to apply and utilize cultural contents based on the value of the intangible heritage of Gyeonggi Geommu, an intangible cultural asset. Methods: Through literature research and existing previous studies, it seeks ways to apply and utilize cultural contents that reflect the contemporary value of Gyeonggi Geommu, an intangible cultural asset. To this end, the significance of intangible heritage and the characteristics of Gyeonggi sword dance are diagnosed. After estimating the three axes for the application and utilization of cultural contents of Gyeonggi sword dance, the following results were derived. Result: First, the Gyeonggi Gummu Cultural Contents plan based on regional uniqueness is the regular Gyeonggi Gummu Festival. Second, the Gyeonggi Geommu cultural contents plan based on national representation is the creation and operation of the Geommu contents platform. Third, as a cultural contents plan for Gyeonggi sword dance based on art transmission, it is a multi-faceted application as a cultural contents for Gyeonggi sword dance, an intangible heritage of the 21st century. Conclusion: It was confirmed that the uniqueness of the cultural circle and the inherentness of traditional dance can be applied and utilized through the connection with various platforms.